An investigation of Salmonella Fluntern illnesses linked to leopard geckos—United States, 2018. (11th September 2019) - Koski, Lia; DeBess, Emilio; Rosen, Hilary E.; Reporter, Roshan; Waltz, Thomas; Leeper, Molly; Concepcion Acevedo, Jeniffer; Karpíšková, Renáta; McCormick, Jacquelyn; Gelbicova, Tereza; Morningstar-Shaw, Brenda; Nichols, Megin; et al.
Abstract: Reptile contact can result in zoonotic non‐typhoidal salmonellosis. In April 2018, Oregon Public Health Division contacted CDC about a cluster of four Salmonella serovar Fluntern (SF) illnesses in four states (OR, CA, IA, NY); patients reported contact with geckos, a popular reptile pet. PulseNet, the national molecular subtyping network of food‐borne disease surveillance, subsequently identified additional SF clinical isolates. Twelve cases in 11 states were identified; median age was 5 years (range: <1–58 years). Three patients were hospitalized; no deaths were reported. Of those with exposure information ( n = 10), all reported reptile exposure; 9 (90%) specified contact with leopard geckos. No common source of geckos was identified from reported purchase locations. Los Angeles County (LAC) health officials isolated SF from one patient's leopard gecko. Five reptile/gecko isolates were identified from the USDA National Veterinary Services Laboratories (NVSL) from 2015 to 2018. Five countries responded to an Epidemic Intelligence Information System post by PulseNet; reptile isolate sequence data were received from Czech Republic. A clinical case from England was identified through the National Center for Biotechnology Information pathogen detection pipeline; the patient did not report contact with leopard geckos. Whole genome sequencing analysis revealed substantial genetic diversity between clinical and animal isolates; however, gecko and clinical isolates from LAC were highly related (1 allele difference). This investigation linking SF illnesses to leopard geckos highlights an important public health risk from pets. A better understanding of how geckos are distributed by the pet industry in the United States could improve traceability to points of origin and mitigate Salmonella transmission at gecko breeders. Earlier NVSL reports of SF isolates from geckos suggest the risk of human SF infection from geckos is not new. This investigation demonstrates a need to educate gecko breeders, retailers and gecko owners about the continued Salmonella infection risk from pet geckos.